Thermoelectric Performance of Spark Plasma Sintered Co4Ge6Te6 Ternary Skutterudite and Doped SnTe Compounds - Aminzare, Masoud (My University, 2018)
A large amount of thermal energy is being wasted every day from domestic and industrial usages such as home appliance and heating system, vehicle exhaust and many industrial processes including melting, refining, annealing, and forming. However, there were a significant impact on the environment and economy if one could recover this waste energy and convert it to useful energy for the industrial or domestic consumptions. Thermoelectric (TE) generators as a direct heat conversion technology are a promising approach to scavenge waste heat and to significantly improve the overall energy efficiency of energy-intensive industries. However, the energy conversion efficiency of current thermoelectric materials is insufficient to make the technology economically viable. In this study, we investigated two potential thermoelectric materials, Co4Ge6Te6 skutterudite and SnTe, in order to enhance their TE properties. Among all the state-of-the-art thermoelectric materials, skutterudites have been found to be brilliant candidates for thermoelectric applications due to their remarkable electronic transport properties. Ternary skutterudites are isostructural to their binary analogues with the advantage of lower lattice thermal conductivity than the unfilled binary skutterudites due to the increased structural complexity. Here, in order to further understand this system and its thermoelectric properties, polycrystalline Co4Ge6Te6 (CGT) was investigated as a model ternary skutterudite material. Spark plasma sintering (SPS) was used to solidify the samples. The microstructure, phase stability, compositional homogeneity and thermoelectric behaviour of the sintered samples under SPS condition were investigated. We found that SPS can form different crystalline phases due to the migration of highly mobile species inside the sample due to the applied electrical current. There were significant inconsistencies in the physical properties of the samples. We also realized that Sb-doped CGT samples yielded to the highest power factor reported for the CGT derivatives so far. Moreover, recent environmental regulations have restricted the use of lead in many real-life applications including thermoelectric power generators. SnTe as a lead-free chalcogenide-based material can be a promising TE candidate to attain high thermoelectric performance. However, the main issue with SnTe is high intrinsic Sn vacancies leading to low Seebeck coefficient and high electrical thermal conductivity. In this regard, we aimed to introduce different metallic species into the SnTe samples (Sn1-xAxTe, A= Co, Ni, Zn, Ge, and x = 0.01, 0.03, 0.05) to enhance their TE performance. Each metallic species presented different solubility and microstructural impact on the main SnTe phase and therefore caused variations in physical properties. Ge-doped samples had more uniform microstructures with a very few Ge-rich regions, which implies higher Ge solubility in SnTe matrix. The existence of impurity phases in the Co-, Ni-, Zn-doped samples yields lower lattice thermal conductivities without deterioration in charge transport properties, leading to higher ZT values relative to the pristine SnTe sample. Microhardness of the doped samples is also improved due to the crack growth suppression and crack branching.
Keywords: Thermoelectric; Inorganic Material; Semiconductor; Energy